Postural orthostatic tachycardia syndrome is associated with significant employment and economic loss. (15th February 2021) - Bourne, Kate M.; Chew, Derek S.; Stiles, Lauren E.; Shaw, Brett H.; Shibao, Cyndya A.; Okamoto, Luis E.; Garland, Emily M.; Gamboa, Alfredo; Peltier, Amanda; Diedrich, André; Biaggioni, Italo; Sheldon, Robert S.; et al.
Abstract: Background: Postural orthostatic tachycardia syndrome (POTS) is a debilitating form of chronic orthostatic intolerance that primarily affects women and causes substantial impairment in quality of life and function. Yet, there is minimal literature describing the employment and economic consequences of POTS. We explored these aspects of the POTS patient experience through a self‐reported study designed using community‐based participatory research principles. Methods and results: A comprehensive questionnaire, including employment and economic consequences, was developed in partnership with Dysautonomia International, a patient advocacy organization. The POTS community engaged in all stages of the research design and analysis. Participants were recruited through Dysautonomia International's website and social media channels. The analysis included 5, 556 adult (age ≥18 years) participants with a physician‐confirmed diagnosis of POTS. The majority of participants were female (95%). Forty‐eight per cent of participants reported employment during the three months prior to the survey, and of these participants, 66.8% would work greater hours if not for illness limitations. Over two‐thirds (70.5%) of participants have lost income due to POTS symptoms, with 36.0% of the total cohort losing more than $10, 000 USD in the 12 months prior to the survey. Almost all (95%) participants reported POTS‐related out‐of‐pocket medical expenses since diagnosis, with 51.1% of participants spending $10, 000 USD or more. Conclusions: This is the largest study reporting the employment and economic challenges experienced by individuals with POTS. Exposure of these challenges emphasizes the need for earlier diagnosis and improved therapeutic strategies to reduce the negative individual and societal consequences of this disorder. Abstract :